Prognostic nutritional index for predicting the clinical outcomes of patients with gastric cancer who received immune checkpoint inhibitors - Sun, Hao; Chen, Li; Huang, Rong; Pan, Hongming; Zuo, Yanjiao; Zhao, Ruihu; Xue, Yingwei; Song, Hongjiang (Frontiers in Nutrition, 2022)
Objective: Although the application of immunotherapy in gastric cancer has achieved satisfactory clinical effect, many patients have no response. The aim of this retrospective study is to investigate the predictive ability of prognostic nutrition index (PNI) to the prognosis of gastric cancer patients received immune checkpoint inhibitors (ICIs). Methods: Participants were 146 gastric cancer patients with ICIs (PD-1 / PD-L1 inhibitors) or chemotherapy. All patients were divided into low PNI group and high PNI group based on cut-off evaluated by receiver operating characteristic (ROC) curve. We contrasted the difference of progression free survival (PFS) and overall survival (OS) in two groups, while calculated the prognosis factors for PFS and OS by univariate and multivariate analysis. Moreover, the nomogram based on the results of multivariate analysis was constructed to estimate the 1-, 3-, and 5-year survival probability. Results: There were 41 (28.1%) cases in low PNI group and 105 (71.9%) cases in high PNI group. The median survival time for PFS in low PNI group and high PNI group were 12.30 months vs 33.07 months, and 18.57 months vs not reached in two groups for OS. Patients in low PNI group were associated with shorter PFS and OS in all patients (Hazard ratio [HR] = 1.913, p = 0.013 and HR = 2.332, p = 0.001). And in subgroup analysis, low PNI group cases also had poorer PFS and OS, especially in patients with ICIs. In addition, albumin, prealbumin, carbohydrate antigen 724 (CA724), PNI and TNM stage were found both independent prognostic factors for PFS and OS by multivariate analysis. Conclusions: PNI was an accurate inflammatory and nutritional marker, which could predict the prognosis of gastric cancer patients received ICIs. PNI could be used as a biomarker for ICIs to identify gastric cancer patients who might be sensitive to ICIs.